How To Develop A Christian Religious Education Learning Model With A Blended Learning Approach (Need Analysis Studies) - Olivia Cherly Wuwung; Jeane Marie Tulung (Peneliti.net, 2021)
This study aims to develop a PAK learning model with a blended learning approach. research and development. The results of this study can be concluded that the PAK learning model with the developed blended learning approach is very good and feasible to use and there is an increase in learning outcomes for students who use the PAK learning model with the blended approach